Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/chemengineering2030030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Off-Spec Canola Biodiesel Blending on Fuel Properties for Cold Weather Applications

Abstract: Biodiesel is a renewable and reduced-emission alternative fuel produced mainly from the alcoholysis of vegetable oils and/or animal fats. It is mainly used in blends with diesel fuel to reduce emissions, enhance lubrication and lower sulfur content. Being able to accurately determine the physicochemical properties of blended fuel is important for optimal injection, combustion, and lubricating performance in diesel engines. Also, fuel properties vary as the ratio of biodiesel-diesel changes, affecting the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…34 However, the suggested emulsified fuel's higher cloud point could be a drawback limiting HEDA fuel usage in cold weather engine running circumstances. When biodiesel was combined with diesel, Hassan et al 35 showed similar outcomes.…”
Section: Physicochemical Properties Analysismentioning
confidence: 90%
“…34 However, the suggested emulsified fuel's higher cloud point could be a drawback limiting HEDA fuel usage in cold weather engine running circumstances. When biodiesel was combined with diesel, Hassan et al 35 showed similar outcomes.…”
Section: Physicochemical Properties Analysismentioning
confidence: 90%
“…The objective is to evaluate the quality characteristics of the produced biodiesel through the analysis of the samples, conducted at ELIN Biofuels Laboratories. Determining the properties of the UCO based biodiesel is essential for the optimal injection and combustion performance of diesel engines [29]. Parameters were compared to the maximum and minimum permitted values, according to the Standard EN 14214: 2012 [30].…”
Section: Methodsmentioning
confidence: 99%
“…17 Canola biodiesel is mainly used in diesel blending, reducing carbon emissions, improving lubrication and reducing sulfur content in fuel. 18 Some authors have already studied canola meal, reporting good results for the adsorption of methylene blue and other cationic dyes using low-cost biosorbents from canola wastes 19 or canola shells. 20 In addition, Al-Asheh and Duvnjak 21 conducted a pioneering study that showed the adsorption potential of canola biosorbents for copper removal from water sources.…”
Section: Introductionmentioning
confidence: 99%